ASSESSMENT OF E-WASTE COLLECTION AND DISPOSAL ACTIVITIES IN GOVERNMENT AGENCIES, BUSINESS AND RESIDENTIAL AREAS IN MINNA METROPOLIS, NIGER STATE - Ndidi, Ogbenna Mavis; Emmanuel, Raymond (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
E-waste and its devastating effects on human existence is one major global concern today. This study was designed to Assess E-waste collection and disposal activities in government agencies, business and residential areas in Minna metropolis, Niger State Nigeria. The research adopted a descriptive survey design. The target population was 226,661 and sample of 311respndents was taken from NESREA 34, NISEPA 53, FME 24, USER 100 and REPAIRERS 100 in Minna metropolis Niger State. 22 items of structured questionnaire items were used for data collection. The instrument was validated by three experts and Cronbach Alfa (K-R20) statistic was used to ascertain the extent of homogeneity of the items and the reliability coefficient of 0.89 was obtained. Data was collected and analyzed using statistical package for social science (SPSS version 20), mean and standard deviation were used to answer the research questions, while ANOVA was used to present the hypothesis at 0.05 level of significance. The findings of the study show that E-waste is sorted out from solid waste at the point collection before disposal, E-waste are dumped indiscriminately along the streets and the individual that generates E-waste is responsible for the disposal. The study recommended among others, that Government should put in place an effective monitoring system for management of e-waste in Niger State Nigeria.